Impacts of long‑term cultivation of flooded rice in gley soils - Marrenjo, Gonçalves Jotamo; de Pádua, Eduane José; Silva, Carlos Alberto; Soares, Plínio César; Zinn, Yuri Lopes (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate soil attributes in response to different land use systems in the south of the state of Minas Gerais, Brazil. The soils sampled were gley soils under native forest, flooded rice (Oryza sativa) and common bean (Phaseolus vulgaris) croplands, as well as a dryland Ultisol under native forest. Cultivation increased bulk density in the gley soils, up to 0.4-m soil depth, which resulted in lower weighted mean diameter and lower geometric mean diameter of aggregates, especially for rice crops under flooding, annually tilled with rotary hoe. Micromorphological analyses of soil showed that soil compaction occurred due to the lower macroporosity among aggregates, as well as to the lower porosity derived from biological activity. Soil organic C (SOC) and total nitrogen (N) in the cultivated gley soils were approximately 55 and 40% lower than in gley soil under native forest, as a consequence of accelerated organic decomposition caused by tillage. However, the gley soil under native forest showed contents and stocks of SOC and N similar to those of the Ultisol under forest, which suggests that the effect of anaerobiosis on soil organic matter was weaker than expected.